A potential roadmap to overcome the current eastern DRC Ebola virus disease outbreak: From a computational perspective - Gaston K. Mazandu; Victoria Nembaware; Nicholas E. Thomford; Christian Bope; Ousmane Ly; Emile R. Chimusa; Ambroise Wonkam (Scientific African, 2020)
The ongoing Ebola virus disease (EVD) outbreak in the eastern Democratic Republic of Congo is raising unprecedented health concerns, with potential to wipe out large proportions of the population in this part of the world. Established control strategies to contain the outbreak are failing due to several reasons, including lack of a data/information repository and ongoing violence and armed conflict. In this paper, we propose a potential roadmap from a computational perspective, which may provide solutions to contain the current outbreak, predict future outbreaks and facilitate development of novel solutions and therapeutics. This roadmap includes the implementation of an integrated information system through a centralized data coordinating center unifying existing and future EVD data and information to enhance innovative EVD translational research. This work will leverage off tools, guidelines and protocols developed by established data coordinating centers based in Africa or centers that address infectious disease outbreaks. The proposed EVD computational strategy is expected to inform optimal strategies at the national or global level towards strengthened responses to future EVD outbreaks and potential emergency of therapy resistant. Keywords: Ebola virus disease, rVSV-ZEBOV, Monoclonal antibody, Translational research, FAIR data